PENGARUH LEVEL PEMBERIAN â€œPUYER HERBALâ€ TERHADAP KECERNAAN, BAHAN KERING, BAHAN ORGANIK DAN LEMAK KASAR PADA AYAM BROILER. - Kulla, Harun; Supartini, Nonok; Iskandar, Ahmad (Universitas Tribhuwana Tunggadewi, 2018)
Consumer demand for meat commodities as a source of animal protein is currently quite high. Poultry meat is an excellent commodity to be developed as a strategic commodity, especially in terms of fulfilling the nutritional needs, health, and living standards of the community. To achieve the success of the broiler farm business, not only requires large capital and adequate skills, but also the management and marketing of reliable production. The purpose of this study is to determine the effect of different levels of powder herbs against dry matter digestion, organic matter, and crude fat in broiler chickens. The method used is the experimental method and complete randomized design (RAL). Treatment of P0 = Giving rations without herb powder, P1 = feeding + herbs 0.3%, P2 = ration + herb pepper 0.6%, P3 = ration + herb pepper 0.9%. The results of research, it can be concluded that the provision of herbal powder does not give a significant different effect of the four treatments on the digestibility of dry matter and organic materials but significantly different from the grease fat digestibility. The highest digestibility was found in P2 treated with herb powder at 0.6%. Permintaan konsumen akan komoditi daging sebagai sumber protein hewani saat ini cukup tinggi. Daging unggas merupakan komoditi unggul yang tepat untuk dikembangkan sebagai suatu komoditi strategis, terutama dalam hal pemenuhan kebutuhan nutrisi, kesehatan, dan taraf hidup masyarakat. Untuk mencapai kesuksesan usaha peternakan ayam broiler, tidak hanya memerlukan modal yang besar dan keterampilan yang memadai, tetapi juga pengelolaan dan pemasaran produksi yang handal. Tujuan dari penelitian ini adalah mengetahui pengaruh perbedaan tingkat puyer herbal terhadap Kecernaan Bahan Kering, Bahan Organik, dan Lemak Kasar pada ayam broiler. Metode yang digunakan adalah metode eksperimen dan rancangan acak lengkap (RAL). Perlakuan penilitian P0 = Pemberian ransum tanpa puyer herbal, P1 = pemberian ransum + puyer herbal 0,3%, P2 = pemberian ransum + puyer herbal 0,6%, P3 = pemberian ransum + puyer herbal 0,9%. Hasil penilitian, maka dapat di simpulkan bahwa pemberian puyer herbal memberikan pengaruh yang nyata terhadap kecernaan bahan kering dan bahan organik namun berbeda nyata dengan kecernaan lemak kasar. Kecernaan tertinggi terdapat pada perlakuan P2 yang di berikan puyer herbal sebesar 0,6%.